Produção de milho verde, seco e para silagem sob doses de nitrogênio fertirrigadas em duas safras de cultivo no semiárido brasileiro - Souza, Ênio Gomes Flôr (2018)
The producers in the northeastern semi-arid region of Brazil have cultivated maize irrigated, aiming mainly at the commercialization of green ears and silage. However, the irrigated crop for dry grains has questions about the costs and price competitiveness in relation to the non-irrigated product, originating in other regions. In recent years, the use of drip tapes and fertigation has spread among maize producers in the region. Nitrogen (N) is the nutrient most demanded by maize, in which increasing doses can increase the yield. The aim of this study was to determine the N dose via fertigation, which provides the maximum economic production of maize for green ears, silage and dry grains, in two agricultural crops (summer and winter), located in the municipality of Canindé de São Francisco, State of Sergipe, Brazilian semi-arid. The experimental design was in randomized blocks, with four replications. In both crops, the treatments consisted of four doses of N (0, 80, 160 and 240 kg ha-1) in the form of urea. In the hybrid maize Bt Feroz, when green, were evaluated the N content in the diagnostic leaf, the number and mass of ear (total and marketable). In maize for silage: yeld of fresh and dry mass of the shoot. For dry grains: plant height and ear insertion, stalk diameter, 100 grain mass and grain yield. For all products, the total costs of production, gross and net incomes, rate of return and profitability index were calculated for each dose of N and agricultural crop. Joint analyzes were performed for the characteristics with homogeneity of variances between the agricultural crops. For green maize, the highest numbers of marketable ears were reached with 152.52 kg ha-1 of N in summer (41,183.84 ha-1) and 190.31 kg ha-1 of N in winter (53,291.25 ears ha-1). The net income reached maximum values of R$ 13,473.50 ha-1 (summer) and R$ 18,266.30 ha-1 (winter), when fertigations were applied with 146.58 and 185.83 kg ha-1 of N, respectively. In the summer harvest of maize for silage, fresh mass yield (26.92 t ha-1) and net income (R$ 4,318.94 ha-1) were highest when the plants were fertigated with 87.62 and 71,14 kg ha-1 of N, respectively. In the winter, the fresh mass yield (38.14 t ha-1) and the net income (R$ 8,322.79 ha-1) of maize for silage increase up to the dose of 240 kg ha-1 of N. Independent of agricultural crops, the yield of dry grains (5,441.03 kg ha-1) was highest when the maize was fertigated with the dose of 104.05 kg ha-1 of N. The highest net incomes of dry grains were observed at 80 kg ha-1 of N in summer (R$ 1,190.78 ha-1) and 160 kg ha-1 of N in winter (R$ 2,757.54 ha-1). The winter crop was more favorable to the economic production of green ears, silage and dry grains